Acute deletion of the central MR/GR steroid receptor correlates with changes in LTP, auditory neural gain, and GC-A cGMP signaling - Calis, Dila; Hess, Morgan; Marchetta, Philine; Singer, Wibke; Modro, Julian; Nelissen, Ellis; Prickaerts, Jos; Sandner, Peter; Lukowski, Robert; Ruth, Peter; Knipper, Marlies; Rüttiger, Lukas (Frontiers in Molecular Neuroscience, 2023)
Abstract The complex mechanism by which stress can affect sensory processes such as hearing is still poorly understood. In a previous study, the mineralocorticoid (MR) and/or glucocorticoid receptor (GR) were deleted in frontal brain regions but not cochlear regions using a CaMKIIα-based tamoxifen-inducible CreERT2/loxP approach. These mice exhibit either a diminished (MRTMXcKO) or disinhibited (GRTMXcKO) auditory nerve activity. In the present study, we observed that mice differentially were (MRTMXcKO) or were not (GRTMXcKO) able to compensate for altered auditory nerve activity in the central auditory pathway. As previous findings demonstrated a link between central auditory compensation and memory-dependent adaptation processes, we analyzed hippocampal paired-pulse facilitation (PPF) and long-term potentiation (LTP). To determine which molecular mechanisms may impact differences in synaptic plasticity, we analyzed Arc/Arg3.1, known to control AMPA receptor trafficking, as well as regulators of tissue perfusion and energy consumption (NO-GC and GC-A). We observed that the changes in PPF of MRTMXcKOs mirrored the changes in their auditory nerve activity, whereas changes in the LTP of MRTMXcKOs and GRTMXcKOs mirrored instead the changes in their central compensation capacity. Enhanced GR expression levels in MRTMXcKOs suggest that MRs typically suppress GR expression. We observed that hippocampal LTP, GC-A mRNA expression levels, and ABR wave IV/I ratio were all enhanced in animals with elevated GR (MRTMXcKOs) but were all lower or not mobilized in animals with impaired GR expression levels (GRTMXcKOs and MRGRTMXcKOs). This suggests that GC-A may link LTP and auditory neural gain through GR-dependent processes. In addition, enhanced NO-GC expression levels in MR, GR, and MRGRTMXcKOs suggest that both receptors suppress NO-GC; on the other hand, elevated Arc/Arg3.1 levels in MRTMXcKOs and MRGRTMXcKOs but not GRTMXcKOs suggests that MR suppresses Arc/Arg3.1 expression levels. Conclusively MR through GR inhibition may define the threshold for hemodynamic responses for LTP and auditory neural gain associated with GC-A.